Altered structural covariance networks in nonsuicidal self-injury: Implications for socio-affective dysfunctions - Soo-Eun Lee; Ji-Won Hur (NeuroImage, 2025)
Nonsuicidal self-injury (NSSI) is a serious behavior that emerges during adolescence and young adulthood, a time of substantial cortical development and challenges in coping with social and emotional stress. However, there is a significant gap in research regarding the neurophysiological basis that may underlie socio-affective difficulties in individuals with NSSI. This study aimed to address this gap by examining changes in structural covariance networks (SCNs) and their associations with socio-affective dysfunctions in individuals with NSSI. Sixty-one individuals with NSSI and 62 healthy controls completed anatomical T1-weighted MRI scans and self-report questionnaires on emotion dysregulation and emotional contagion. Individualized SCNs were constructed using cortical thickness measures, and graph theoretical analysis was applied to examine the global and regional properties of these networks. Compared to controls, individuals with NSSI exhibited significantly reduced global efficiency, local efficiency, global clustering coefficient, regional nodal strength in the right insula, but increased hubness in the middle posterior cingulate cortex (mPCC). Lower nodal strength in the insula was correlated with diminished positive emotional contagion, while greater hubness in the mPCC was linked to heightened emotion dysregulation in the NSSI group. Taken together, our results provide preliminary evidence suggesting that NSSI may be associated with reduced efficiency in brain network organization, particularly in regions associated with socio-affective functioning. These findings highlight the necessity of targeted interventions that enhance positive emotional contagion and improve emotion regulation strategies, offering a promising direction for clinical practice.